Analysis of Russian Retailers’ Communication Strategies in Terms of External Constraints - STAROSTIN, Vasily S.; CHERNOVA, Veronika Y. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The research subject includes Russian retailers working under current crisis conditions. The research is aimed at identifying specific features in the retail and developing the upcoming directions in communication strategies. The research relevance depends on the fact that the communication strategies currently used by retailers are aimed at meeting the immediate needs of customers, therefore it is reasonable to develop the most promising directions of consumer engagement that require changes to the retailers’ communication strategies to increase their performance. The research uses the systematic approach to identify the mentioned features and determine existing structural interrelations between the factorial and performance indicators of retailers’ activities. The completed statistical analysis of the retail trade dynamics in Russia shows that despite the increased sales, the market share of the Russian retailers has gradually decreased, giving way to other trade formats. It has become clear that we need to transform the communication strategies to expand the market share, attract consumers, and ensure a sustained growth of companies. The authors have submitted the approach to the improvement of the communication strategies by raising an interest of consumers in a particular company.